2018
DOI: 10.7554/elife.33549
|View full text |Cite
|
Sign up to set email alerts
|

A robust and tunable mitotic oscillator in artificial cells

Abstract: Single-cell analysis is pivotal to deciphering complex phenomena like heterogeneity, bistability, and asynchronous oscillations, where a population ensemble cannot represent individual behaviors. Bulk cell-free systems, despite having unique advantages of manipulation and characterization of biochemical networks, lack the essential single-cell information to understand a class of out-of-steady-state dynamics including cell cycles. Here, by encapsulating Xenopus egg extracts in water-in-oil microemulsions, we d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 38 publications
3
51
0
Order By: Relevance
“…Metabolic reprogramming has been widely accepted as a distinctive hallmark of cancer. Cancer cells exhibit increased glucose uptake, enhanced glycolysis and lactate production, and reduced oxygen consumption, even in oxygen-rich conditions, known as the Warburg effect or aerobic glycolysis [24][25][26]. In addition to promoting tumorigenesis, aerobic glycolysis plays a vital role in developing drug resistance [27].…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic reprogramming has been widely accepted as a distinctive hallmark of cancer. Cancer cells exhibit increased glucose uptake, enhanced glycolysis and lactate production, and reduced oxygen consumption, even in oxygen-rich conditions, known as the Warburg effect or aerobic glycolysis [24][25][26]. In addition to promoting tumorigenesis, aerobic glycolysis plays a vital role in developing drug resistance [27].…”
Section: Discussionmentioning
confidence: 99%
“…As already mentioned, reductions in cell size over early development are driven by rapid cell divisions without cell growth, so cell cycle timing is a key determinant of cell size in the early embryo. There is also evidence that cell size and cytoplasmic volume determine cell division timing, with cell size reductions leading to increased cell cycle lengths (Arata & Takagi, 2019;Guan et al, 2018;Masui & Wang, 1998). Characteristic of many early developmental programs, asymmetric cell divisions give rise to different sized cells within the embryo (Cadart, Zlotek-Zlotkiewicz, Le Berre, Piel, & Matthews, 2014).…”
mentioning
confidence: 99%
“…It has been established that size and confinement have a considerable impact on TXTL reactions [45,46]. For this reason, more attention should be paid to implementing TXTL reactions in liposomes of defined size and dispersity.…”
Section: Discussionmentioning
confidence: 99%
“…encapsulated Xenopus egg extract in microdroplets of various size. The authors showed that the extract could undergo several mitotic oscillations, and described the influence of the size of the compartments on the period [45]. Sakamoto et al .…”
Section: Engineered Compartments To Study Physicochemical Properties mentioning
confidence: 99%